The Influence of Entrepreneurial Education and Entrepreneurial Mindset on Entrepreneurial Intention Throgh Self-Efficacy : Study on Business and Marketing Students in Banyuwangi - Prayitno, Reza Dwi; Rahayu, Wening Patmi; Wardhana, Ludi Wishnu (PT. BATARI EDU CALYA, 2024)
This study aims to examine the influence of Entrepreneurial Education and Entrepreneurial Mindset on Entrepreneurial Intention through Self- Efficacy. The goals of this study are to ascertain: (1) The direct effect of Entrepreneurial Education on Self-Efficacy, (2) The direct effect of Entrepreneurial Mindset on Self-Efficacy, (3) The direct effect of Entrepreneurial Education on Entrepreneurial Intention, (4) The direct effect of Entrepreneurial Mindset on Entrepreneurial Intention, (5) The direct effect of Self-Efficacy on Entrepreneurial Intention, (6) The indirect effect of Entrepreneurial Education on Entrepreneurial Intention through Self-Efficacy, and (7) The indirect effect of Entrepreneurial Mindset on Entrepreneurial Intention through Self-Efficacy. This study utilizes a quantitative methodology, including descriptive and explanatory research techniques. The research included a total of 293 students as participants, specifically those enrolled in Business and Marketing majors. The sample is collected accidentally by distributing questionnaires as part of a mix of purposeful and accidental sampling via Google Forms and considering criteria relevant to the research objectives. SEM-PLS and descriptive statistics are two examples of data analysis methodologies